Landasan Perilaku dalam Kegiatan Pembelajaran Based Teknologi - Al Mubarok, Itsnan Mahfuddin; Pratiwi, Intan; Munawaroh, Lailatul; Rahayu, Mikha Istria Puji (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Writing articles on Technology-Based Learning by applying the basis of behavior. In writing this article aims to explain the relevance of the basis of behavior in technology-based learning activities. In the process of research and preparation of this article, researchers used a qualitative research approach to library research. The results of the research show that the foundation of behavior in technology-based learning activities is very relevant because educational technology strengthens the engineering of various methods and techniques from the design, development, utilization of various learning resources, implementation, and assessment of programs and learning outcomes.